Cardiogenic shock following acute MI in a young patient with familial hypercholesterolemia, and severe aortic stenosis: A case report. Issue 12 (December 2022) - Davoodabadi, Zeinab; Hosseini, Zahra; Norouzi, Somayyeh; Davoodabadi, Hassan; Sheikh-Sharbafan, Reza; Ghodsi, Saeed
Abstract: Background: Familial hypercholesterolemia is a relatively rare disorder with various clinical manifestations including premature coronary artery disease. Case presentation: A 15-year-old boy presented with acute exacerbation of dyspnea and exertional chest pain with a progressive feature since one month earlier. He had a clustered family history of premature cardiovascular death, hyperlipidemia, and cutaneous lesions in two of his siblings. He presented with acute severe heart failure accompanied with high levels of cardiac troponin and LDL cholesterol. Echocardiography revealed severe LV dysfunction, in concert with valvular and supravalvular Aortic stenosis. He underwent Coronary angiography, which showed involvement of Left main coronary artery and two-vessel disease. The patient was diagnosed with cardiogenic shock secondary to acute non-ST segment elevation myocardial infarction, and phenotype of familial hypercholesterolemia. Conclusions: Premature malignant atherogenesis in both aortic root and coronary arteries with early presentation of acute myocardial infarction and severe heart failure is an uncommon constellation in early course of the FH, which leads to confined treatment options. Abstract : Familial hypercholesterolemia; Myocardial infarction; Heart failure; Aortic stenosis; Coronary artery disease.